Lacerated Tongue Injury in an Infant: A Case Report - Gurung, Pratistha; Shrestha, Sneba; Dali, Mamta; Koirala, Bandana (Journal of Nepalese Association of Pediatric Dentistry, 2020)
Tongue laceration is not uncommon in young children. The most common location for a lacerated tongue injury in children is the anterior dorsum of the tongue. Fall at home is the most common cause of injury. Choosing an optimal treatment option for tongue lacerations remains a challenge due to contradictory recommendations and lack of current guidelines. This case reports the timely intervention and repair of a lacerated tongue injury in an 11-month-old infant under local anesthesia with satisfactory healing where function and esthetics of the tongue was restored. Thus, timely intervention of suturing in lacerated tongue injury in children can give good results.